GROWTH OF Trachelomonas sp. AS A STEP FOR HEAVY METAL TOXICITY TEST - Dormegawaty, Adonia; Budijono, Budijono; M. Hasbi, M. Hasbi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstractThis study is aimed to learn the capabilities of Trachelomonas sp. as biotaqualifies for metal toxicity test. This research is done for 17 days by seeing an entireliving phase of Trachelomonas sp. in the growth curve. A cell density analysis fromTrachelomonas sp.calculated using a microscope.This result indicate that there are4 living phases of Trachelomonas sp. it’s composed of phases lag, an exponentialphase, stationary phases and phases leading to death. Trachelomonas sp. qualifiedas a test biota for a heavy metal toxicity test using phytoplankton according to Asean-Canada Cooperative Programme on Marine Science Phase II. This is seen from thegrowth of cell density that exceeds the minimum limit on the 4th day of inoculationgrowth curve or at the beginning of an exponential phase with density of cell 1,01 x106cell.mL-1.Keywords : Density. Exponential, Phytoplankton,Trachelomonas sp.,ToxicityTest